2006
DOI: 10.1152/ajpregu.00305.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sex and estrous cycle differences in the behavioral effects of high-strength static magnetic fields: role of ovarian steroids

Abstract: Advances in magnetic resonance imaging are driving the development of higher-resolution machines equipped with high-strength static magnetic fields (MFs). The behavioral effects of high-strength MFs are largely uncharacterized, although in male rats, exposure to 7 T or above induces locomotor circling and leads to a conditioned taste avoidance (CTA) if paired with a novel taste. Here, the effects of MFs on male and female rats were compared to determine whether there are sex differences in behavioral responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
(105 reference statements)
2
14
1
Order By: Relevance
“…Previous reports have not found gender differences [7,9], but there is some evidence for such differences in the effects of various types of magnetic field [26][27][28][29][30][31]. Our results do not agree with some studies in which suicide numbers were found to be inversely related to geomagnetic activity [12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports have not found gender differences [7,9], but there is some evidence for such differences in the effects of various types of magnetic field [26][27][28][29][30][31]. Our results do not agree with some studies in which suicide numbers were found to be inversely related to geomagnetic activity [12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…In male rats, the relationship was a positive correlation, but in female rats the relationship was a negative correlation. This finding corresponds with evidence for sex differences in the effects of various types of magnetic field [12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
“…Sexual steroids are also thought to play a role in the long term persistence of taste aversion: in ovariectomized rats taste aversion was found to be more prominent; however, estrogen replacement eliminated the aversive behavior. Male rats acquired a stronger initial aversion but extinguished faster than females [Cason et al, 2006]. Repeated exposure to SMF attenuates this biological response possibly due to habituation to vestibular perturbation subsequent to the exposure [Houpt et al, 2010].…”
Section: Aversiveness To Moderate Smf Exposurementioning
confidence: 94%